Kaji Tindak Penyusunan Media Pemasaran Berbasis Web Blog Industri Sentral Kacang Tanah Sangrai Di Kelurahan Kranggan, Tangerang Selatan - Suparman Suparman; Nazila Aulia Az-Zahra; Fildzah Nisrina Farhani; Nia Aprilia; Maulidya Khoirunisa; Tito Siswanto (Indonesian Journal of Economics Application (IJEA), 2018)
There are many research results which stated that one of the obstacles faced by the SMEs is a weak of marketing activities. Based such research, this article presents the results of an action research of the designing internet-based marketing which utilize web blog. The focus of the research is directed at peanuts small industry in Kranggan subdistrict, South Tangerang city. The procedure of the action is presented further in this article.